Ventricular septal defect and aortic regurgitation. Issue 3 (May 1969) - Hallidie-Smith, K. A.; Olsen, E. G. J.; Oakley, C. M.; Goodwin, J. F.; Cleland, W. P.
Abstract : We have reviewed our experience of 29 patients with the association of ventricular septal defect and aortic regurgitation, 27 of whom have been treated surgically. Our present approach to the surgical management is outlined and the embryology and pathological anatomy are reviewed. The most common cause of aortic regurgitation was a prolapsed aortic valve cusp, which occurred in 19 patients. Aneurysmal dilatation of an aortic sinus accounted for the regurgitation in three patients, and two patients had both abnormalities. In two patients no cause for the aortic regurgitation was found. Those patients with aortic cusp prolapse commonly had large ventricular septal defects, of which nearly a third were supracristal. Because of cusp prolapse into the ventricular septal defect, and sometimes into the right ventricular outflow tract, the findings at cardiac catheterization often suggested erroneously that the ventricular septal defect was small and that infundibular obstruction was present. Characteristic angiographic features have been demonstrated, in particular the deformed and prolapsed aortic cusp. The various techniques of surgical correction which were used are described, the majority of patients having had a patch closure of the ventricular septal defect and repair of the aortic valve. Some residual aortic regurgitation was usual, but it was improved or minimized in 18 of the 23 survivors, and the more recent results have been particularly encouraging. Closure of the ventricular septal defect alone relieved heart failure in a 3-year-old child. There were four operative deaths (15% mortality) in patients with severe aortic regurgitation, three of whom were in heart failure before operation. The medical course was commonly of slowly increasing severity of the aortic regurgitation with progression to heart failure. However, the individual course was unpredictable and three children developed heart failure within a year of the onset of their aortic regurgitation. Infective endocarditis occurred in a quarter of the patients and usually followed the development of the aortic regurgitation. Despite the difficulties of surgical management it is felt that the unpredictable prognosis, high operative risk once cardiac failure has supervened, and the hazard of infective endocarditis make early operation desirable.